Let's calculate each expression step by step:
-
11 - 6 + 3
- First: 11 - 6 = 5
- Then: 5 + 3 = 8
- Result: 8
-
6 + 11 - 3
- First: 6 + 11 = 17
- Then: 17 - 3 = 14
- Result: 14
-
3 + 11 - 6
- First: 3 + 11 = 14
- Then: 14 - 6 = 8
- Result: 8
-
11 + 3 - 6
- First: 11 + 3 = 14
- Then: 14 - 6 = 8
- Result: 8
Now we summarize the results:
- 11 - 6 + 3 = 8
- 6 + 11 - 3 = 14
- 3 + 11 - 6 = 8
- 11 + 3 - 6 = 8
From these calculations, the expression 6 + 11 - 3 has a different answer (14) compared to the others which all equal 8.